Police response to mental health in Canada - Williams, Uzma (Canadian Scholars, 2019)
Introduction to Mental Health for Policing Professions / Shea-Lyn Boychuk and Uzma Williams -- Bipolar and Other Mood Disorders / Stephanie J. Laue and John R. Reddon -- Schizophrenia and Other Psychotic Disorders / Alberto Choy -- Substance Use Disorders / Adam Howorko and Rick Csiernik -- Antisocial and Other Personality Disorders / Andrew M. Haag -- Childhood Conduct and Other Childhood Disorders / Nicol Patricny, Erin Newman, John R. Reddon, and Salvatore B. Durante -- Paraphilic and Other Sexual Disorders / Debra Jellicoe -- Acute and Post-Traumatic Stress Disorders / Stephanie J. Laue and John R. Reddon -- Police Legitimacy, Interpersonal Response, and Community Trust / Dan Jones, Shea-Lyn Boychuk, Abigail Smith and Uzma Williams -- Police Behavioural Response to Critical Intervention and Emergency Situations / Dan Jones, Lydia Fleming, Jaqueline Brodbin, April Langille, and Uzma Williams -- Police Response to Crisis Involving Suicide Risk: Strategies for Suicide Intervention and Prevention / Jennifer A.A. Lavoie and Scott Blandford -- Mental Health Services and Special Intervention Teams / Debra Jellicoe and Tanya Anderson -- Mental Health of Police Professions and First Responders / Patricia L. Schuster and Graham E. Ross -- The History of Policing and Indigenous Persons in Canada / Dan Jones and Peter Jensen -- NCRMD Legal and Ethical Issues / Courtney J. Hunt, John R. Reddon, Andrew M. Haag, and Salvatore B. Durante -- Letters to Policing Professionals / Kyle L. Klein.